2019
DOI: 10.1111/myc.12998
|View full text |Cite
|
Sign up to set email alerts
|

Towards a rapid identification and a novel proteomic analysis for dermatophytes from human and animal dermatophytosis

Abstract: Summary Background Since accurate identification of dermatophyte species is essential for epidemiological studies and implementing antifungal treatment, overcoming limitations of conventional diagnostics is a fruitful subject. Objectives and methods In this study, we investigated real‐time polymerase chain reaction(q‐PCR), matrix‐assisted laser desorption/ionisation time of flight mass spectrometry (MALDI‐TOF MS) and nano‐electrospray ionisation mass spectrometry (nano‐ESI‐MS) to detect and identify the most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 44 publications
1
26
0
3
Order By: Relevance
“…Increasingly, molecular biology techniques are adapted to the identification of dermatophytes and are more effective than conventional tests [8]. Several techniques for analyzing the genome of dermatophytes have been proposed, and DNA barcoding is very useful for accurate determination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, molecular biology techniques are adapted to the identification of dermatophytes and are more effective than conventional tests [8]. Several techniques for analyzing the genome of dermatophytes have been proposed, and DNA barcoding is very useful for accurate determination.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques for analyzing the genome of dermatophytes have been proposed, and DNA barcoding is very useful for accurate determination. e polymorphism of the internal transcribed spacers (ITS1 and ITS2) flanking the DNA sequence encoding the 5.8S rDNA is very sensitive and reliable for distinguishing different species of dermatophytes [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…MALDI‐TOF MS has proven to be useful for filamentous fungi 12 . A recent report showed that the Bruker MALDI‐TOF MS exhibited a limited ability to identify dermatophytes with Bruker Filamentous Fungi Library v1.0 13 . The main reason was that the Bruker library contains a limited number of reference species and lacks some dermatophyte species such as T violaceum , T verrucosum and T schoenleinii .…”
Section: Discussionmentioning
confidence: 99%
“…Metoda MALDI-TOF MS (Matrix-Assisted Laser Desorption/Ionization -Time of Flight -Mass Spec-trometry; desorpcja/jonizacja laserem wspomagana matrycą z pomiarem czasu przelotu i spektrometrią masową) była metodą początkowo zarezerwowaną wyłącznie do badań naukowych, a w laboratoriach mikrobiologicznych pojawiła się około 10 lat temu [33]. Szerokie zainteresowanie tą metodą wynika z jej wysokiej dokładności, szybkości uzyskiwania wyników identyfikacji mikroorganizmów, stosunkowo niskiego kosztu analiz i prostej implementacji do laboratoriów diagnostycznych [15,49]. Niemniej jednak w literaturze naukowej dostępnych jest tylko kilka doniesień oceniających zastosowanie MALDI-TOF MS do identyfikacji dermatofitów [5,10,23,32,40,49,50] Celem niniejszej pracy jest dokonanie przeglądu piśmiennictwa traktującego o zastosowaniu techniki MALDI-TOF MS w diagnostyce dermatomykoz, ze szczególnym uwzględnieniem identyfikacji dermatofitów.…”
Section: Wprowadzenieunclassified
“…Dopiero jednak zmniejszenie rozmiarów spektrometrów masowych, ułatwienie ich obsługi i znaczne obniżenie kosztów tych urządzeń stało się przyczyną ich szerokiego zastosowania nie tylko do badań podstawowych ale również w laboratoriach klinicznych [38]. W metodzie MALDI-TOF MS wykrywane są białka w zakresie mas od 2 do 20 kDa, które reprezentują głównie białka rybosomalne oraz białka metabolizmu podstawowego [49]. Białka te tworzą charakterystyczny dla drobnoustroju "odcisk", który można porównać z profilami białkowymi zawartymi w bibliotece widm referencyjnych [38].…”
Section: Identyfikacja Drobnoustrojów Z Zastosowaniem Metody Maldi-tounclassified